A preliminary investigation of Stroop-related intrinsic connectivity in cocaine dependence: associations with treatment outcomes. (4th November 2013) - Mitchell, Marci R.; Balodis, Iris M.; DeVito, Elise E.; Lacadie, Cheryl M.; Yeston, Jon; Scheinost, Dustin; Constable, R. Todd; Carroll, Kathleen M.; Potenza, Marc N.
Abstract: Background : Cocaine-dependent individuals demonstrate neural and behavioral differences compared to healthy comparison subjects when performing the Stroop color-word interference test. Stroop measures also relate to treatment outcome for cocaine dependence. Intrinsic connectivity analyses assess the extent to which task-related regional brain activations are related to each other in the absence of defining a priori regions of interest. Objective : This study examined 1) the extent to which cocaine-dependent and non-addicted individuals differed on measures of intrinsic connectivity during fMRI Stroop performance; and 2) the relationships between fMRI Stroop intrinsic connectivity and treatment outcome in cocaine dependence. Methods : Sixteen treatment-seeking cocaine-dependent patients and matched non-addicted comparison subjects completed an fMRI Stroop task. Between-group differences in intrinsic connectivity were assessed and related to self-reported and urine-toxicology-based cocaine-abstinence measures. Results : Cocaine-dependent patients vs. comparison subjects showed less intrinsic connectivity in cortical and subcortical regions. When adjusting for individual degree of intrinsic connectivity, cocaine-dependent vs. comparison subjects showed relatively greater intrinsic connectivity in the ventral striatum, putamen, inferior frontal gyrus, anterior insula, thalamus and substantia nigra. Non-mean-adjusted intrinsic-connectivity measures in the midbrain, thalamus, ventral striatum, substantia nigra, insula and hippocampus negatively correlated with measures of cocaine abstinence. Conclusion : The diminished intrinsic connectivity in cocaine-dependent vs. comparison subjects suggests poorer communication across brain regions during cognitive-control processes. In mean-adjusted analyses, the cocaine-dependent group displayed relatively greater Stroop-related connectivity in regions implicated in motivational processes in addictions. The relationships between treatment outcomes and connectivity in the midbrain and basal ganglia suggest that connectivity represents a potential treatment target.